Inventory of U.S. 2012 dioxin emissions to atmosphere. (December 2015) - Dwyer, Henri; Themelis, Nickolas J.
Highlights: Hitherto unpublished data on 57 U.S. WTE plants representing over 89% of the U.S. WTE capacity. Inventory of all anthropogenic and natural sources of toxic dioxin/furan emissions. Quantitative ratio of total/toxic dioxins of 57 waste-to-energy plants. % of U.S. total (anthropogenic + natural) emissions of dioxins due to waste-to-energy plants. Abstract: In 2006, the U.S. EPA published an inventory of dioxin emissions for the U.S. covering the period from 1987–2000. This paper is an updated inventory of all U.S. dioxin emissions to the atmosphere in the year 2012. The sources of emissions of polychlorinated dibenzodioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs), collectively referred to in this paper as "dioxins", were separated into two classes: controlled industrial and open burning sources. Controlled source emissions decreased 95.5% from 14.0 kg TEQ in 1987 to 0.6 kg in 2012. Open burning source emissions increased from 2.3 kg TEQ in 1987 to 2.9 kg in 2012. The 2012 dioxin emissions from 53 U.S. waste-to-energy (WTE) power plants were compiled on the basis of detailed data obtained from the two major U.S. WTE companies, representing 84% of the total MSW combusted (27.4 million metric tons). The dioxin emissions of all U.S. WTE plants in 2012 were 3.4 g TEQ and represented 0.54% of the controlled industrial dioxin emissions, and 0.09% of all dioxin emissions from controlled and open burning sources.